Comparison of outcomes of second-line durvalumab plus tremelimumab versus lenvatinib following first-line atezolizumab plus bevacizumab in unresectable hepatocellular carcinoma - Chinatsu Nishioka; Yuki Tahata; Kazuki Maesaka; Machiko Kai; Kumiko Shirai; Kazuhiro Murai; Yuki Makino; Yoshinobu Saito; Yasutoshi Nozaki; Tasuku Nakabori; Hisashi Ishida; Takayuki Yakushijin; et al. (PLoS ONE, 2026)
Background and Aim The optimal second-line therapy following first-line atezolizumab plus bevacizumab remains unascertained. In this study, we compared second-line durvalumab plus tremelimumab with lenvatinib after first-line atezolizumab plus bevacizumab in patients with unresectable hepatocellular carcinoma (uHCC). Methods In this retrospective, open-label, non-randomized comparative study, we analyzed real-world data derived from a prospectively registered observational cohort of patients with uHCC who received durvalumab plus tremelimumab (the Dur/Tre group, n = 14) or lenvatinib (the Len group, n = 67) as second-line therapy after first-line atezolizumab plus bevacizumab. Tumor response was assessed using the RECIST criteria version 1.1. Progression-free survival (PFS), overall survival (OS), adverse events (AEs), and changes in the albumin–bilirubin (ALBI) score were compared between the groups. Results The objective response and disease control rates were 7.7% and 15.4% in the Dur/Tre group and 23.3% and 76.7% in the Len group, respectively. The median PFS was 1.7 vs. 4.2 months (p < 0.001) and median OS was 5.3 vs. 14.0 months (p = 0.047) in the Dur/Tre and Len groups, both significantly favoring lenvatinib. Multivariable analysis showed that lenvatinib treatment was an independent predictor of longer PFS, and a neutrophil-to-lymphocyte ratio ≥ 3 was an independent predictor of worse OS. Grade ≥ 3 AEs were more frequent with lenvatinib than with durvalumab plus tremelimumab (70.1% vs. 21.4%; p = 0.002). At week 4, the ALBI score was maintained with durvalumab plus tremelimumab (−2.30 to −2.21; p = 0.318) but worsened with lenvatinib (−2.36 to −1.97; p < 0.001). Conclusions After first-line atezolizumab plus bevacizumab, second-line lenvatinib achieved superior disease control and longer survival than durvalumab plus tremelimumab. However, grade ≥ 3 AEs were more frequent with lenvatinib than with durvalumab plus tremelimumab. Careful AE management is therefore important when selecting therapy for individual patients.